Your research project - Walliman, Nicholas (Los Angeles : Sage Publications, 2011)
"In the third edition of this bestselling book, you'll find everything you need to embark upon your research project and write your proposal with confidence...[this book] will guide you through the process of formulating a research question, choosing your research methods, planning your research, and writing your proposal"--P. [4] of cover.
Research and the research problem -- Research theory and the nature of knowledge -- Concepts, language and argument -- Information, and how to deal with it -- Research methods -- Honesty and research ethics -- Preparing the research proposal and starting to write.
Keywords: Report writing; Research